Diagnostic and therapeutic considerations in Turner syndrome - Seung Yang (Korean Society of Pediatric Endocrinology, 2017)
Newly developed genetic techniques can reveal mosaicism in individuals diagnosed with monosomy X. Noninvasive prenatal diagnosis using maternal blood can detect most fetuses with X chromosome abnormalities. Low-dose and ultralow-dose estrogen replacement therapy can achieve a more physiological endocrine milieu. However, many complicated and controversial issues with such treatment remain. Therefore, lifetime observation, long-term studies of health problems, and optimal therapeutic plans are needed for women with Turner syndrome. In this review, we discuss several diagnostic trials using recently developed genetic techniques and studies of physiological hormone replacement treatment over the last 5 years.